Semiotic analysis of portrait drawing problem - Kudžma, Ričardas; Rukaitė, Vitalija (Lietuvos matematikos rinkinys, 2015)
In this article full semiotic analysis of portrait drawing problem is presented. Two texts are being considered, one from the book of H.B. Griffiths and A.J. Oldknow and other from Vilnius University students control test. Main result is the semiotic square of the text.